1999
DOI: 10.1046/j.1442-200x.1999.4121048.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bioelectrical impedance analysis and dual energy X-ray absorptiometry for assessment of body composition in children

Abstract: Bioelectrical impedance analysis seems to be a reasonable method for daily clinical use, but attention should be paid to the interpretation of %fat values in underweight and overweight children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
1
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 10 publications
7
33
1
4
Order By: Relevance
“…Even equations that were unbiased displayed this underestimation and most childhood studies show similar results. 6,8,10,11 The findings of the current study closely match the BIA findings of Bray et al 1 Although their criterion was the fourcompartment model and ours was DEXA, common equations between both studies 1,5,17,19 show similar results when viewing participants of comparable body fat. For example, the Bray equation resulted in a mean difference close to zero in both studies, and the slopes of the Bray, Deurenberg and Suprasongsin equations were significantly different from zero in both studies.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Even equations that were unbiased displayed this underestimation and most childhood studies show similar results. 6,8,10,11 The findings of the current study closely match the BIA findings of Bray et al 1 Although their criterion was the fourcompartment model and ours was DEXA, common equations between both studies 1,5,17,19 show similar results when viewing participants of comparable body fat. For example, the Bray equation resulted in a mean difference close to zero in both studies, and the slopes of the Bray, Deurenberg and Suprasongsin equations were significantly different from zero in both studies.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, the Kushner equation does not appear to be subject to any systematic error when applied to an African-American adolescent female sample. In fact, none of the equations appear to be subject to any systematic error related to the ethnicity of the sample because the equations provide similar estimates when applied to primarily Caucasian samples 1,5,8,10 as they did in our exclusively AfricanAmerican sample. However, our results are preliminary because the equations were utilized in an exclusively African-American adolescent female sample.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, the children who had higher body fat percentage did not have a larger difference between the two measurements. One study with 10 obese children found a trend to underestimate BIA in relation to DXA measurements (Okasora et al, 1999). In healthy adults another study found a difference of 3.3% between BIA and DEXA, but a gender difference could not be detected (Levenhagen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Данные о сопо-ставимости результатов БИА и ДРА у детей крайне противоречивы. Ряд авторов [11][12][13][14] указывают на их сопоставимость, особенно при определении ко-личества тощей массы как у детей с ожирением, так и без избытка массы тела. Другие [15,16] считают, что данные методы не эквивалентны и не взаимо-заменяемы, а для детской популяции необходима разработка отдельных нормативов в зависимости от пола, возраста и стадии полового развития.…”
Section: биоимпедансный анализunclassified